HLA-G Molecules in Autoimmune Diseases and Infections - Rizzo, Roberta; Bortolotti, Daria; Bolzani, Silvia; Fainardi, Enrico (Frontiers in Immunology, 2014)
Human leukocyte antigen (HLA)-G molecule, a non-classical HLA-Ib molecule, is less polymorphic when compared to classical HLA class I molecules. HLA-G was first detected on cytotrophoblast cells at the feto-maternal interface but its expression is prevalent during viral infections and several autoimmune diseases. . HLA-G gene is characterized by polymorphisms at the 3' untranslated region and 5’ upstream regulatory region that regulate its expression and are associated with autoimmune diseases and viral infection susceptibility, creating an unbalanced and pathologic environment. This review focuses on the role of HLA-G expression in autoimmune conditions and viral infections.